KIMEHS Proposal of an Index for Qualitative Evaluation of Childrens Menus: A Pilot Study - Rocha, Ada (2020)
Considering the importance of the food environments for health promotion, and the lack of simple, easy to use, low-cost measures of the quality of meals, the authors developed a qualitative menu index (KIMEHSKids Menu Healthy Score), tailored to childrens menu evaluation. Development of the tool was based on the Mediterranean food pattern. It includes 18 components, divided into seven main groups that reflect key aspects of menu quality, including protein source, side dishes, vegetables, dessert and beverages, and also allergens and nutritional information. The index was analysed for content and construct validity, as well as inter-rater reliability, and was applied to a sample of menus from restaurants in shopping centres in the Lisbon region. Possible index point ranges from 17 to 17, with a higher score indicating greater compliance with the recommendations. A value of 5.5 is obtained if all KIMEHS items are available, considering healthy and non-healthy options. The inter-rater reliability was assessed and values above 0.80 were obtained for Alpha Cronbach, as well as agreement % rate >75%. Agreement percentage is above 75% for all the components. Evaluated restaurants scored from 14 to 7, with an average KIMEHS of 6.15. Only four restaurants scored positive values, ranging from 0.25 to 7. KIMEHS was considered to be an adequate index to evaluate childrens menus, from the menu information displayed on restaurant websites and/or on restaurant displays or table menus. It is a simple, low-cost tool that may be used as a reference for health professionals as an objective measure to evaluate the food environment. Stakeholders could also be involved in their own assessment to help educate consumers about healthy food choices, strengthening the efforts to promote an adequate food pattern and health, contributing to the fight against obesity.